Register von Hämophilie-Zentren in Deutschland - Zimmermann, R.; Eifrig, B.; Lenk, H.; Pollmann, H.; Scharrer, I.; Huth-Kühne, A. (Hämostaseologie, 2012)
An adequate number of qualified haemophilia centres is an essential requirement for effective and cost-efficient haemophilia care. During a reassessment of the delivery of haemophilia care in Germany a broad range of criteria relating to structure and quality of the centres were defined and a questionnaire was developed. Results: Of 137 doctors who received the questionnaire, 113 (82%) replied. Based on data related to diagnostic and treatment services, together with voluntary information from PEI forms (Paul Ehrlich Institut, Germany), 72 haemophilia centres were established. Three levels of haemophilia care were defined by the Medical Advisory Council of the German Haemophilia Society. This is in accordance with criteria defined by European working parties. 17 haemophilia centres were designated CCC (Comprehensive Care Centre), 24 were designated HTC (Haemophilia Treatment Centre) and 31 smallest centres were allocated the status HTR (Haemophilia Treatment Regional). In comparison to the survey in 2007, there was only slight variance in the CCC centres (+ 2 centres/–1 centre). From the previous HTC centres, 7 have withdrawn from this treatment level: 4 maintain treatment on the lower level HTR, and 3 centres had ceased treatment. On the HTR level of treatment, 6 of 29 (21%) had ceased to offer treatment. 9 had been able to increase the number of patients and were designated HTC. 5404 patients with haemophilia and 3047 with the severe form of haemophilia were reported. 67% were treated in CCC, 25% in haemophilia treatment centres and 8% in the 31 smallest centres. 13 of the adult CCC are situated in the department of internal medicine and 4 in the section of transfusion medicine. Conclusions: The survey and analysis of the haemophilia treatment centres in Germany show that the delivery of haemophilia care through 17 CCC, 24 HCT and 31 HTR appears to be adequately structured. But it is noticeable and alarming, however, that on both HTC and HTR levels of treatment, 32% and 21%, respectively, have left their treatment level. 9 centres (12.5%) have finished working in haemophilia care in the last four years. On the strength of these results, endeavours to maintain haemophilia centres must be intensified. A high level of effective care can be guaranteed only through continued existence of the centres.
Keywords: Haemophilia; haemophilia management; haemophilia center; comprehensive care center